2020
DOI: 10.3390/microorganisms9010073
|View full text |Cite
|
Sign up to set email alerts
|

Probiogenomics Analysis of 97 Lactobacillus crispatus Strains as a Tool for the Identification of Promising Next-Generation Probiotics

Abstract: Members of the genus Lactobacillus represent the most common colonizers of the human vagina and are well-known for preserving vaginal health and contrasting the colonization of opportunistic pathogens. Remarkably, high abundance of Lactobacillus crispatus in the vaginal environment has been linked to vaginal health, leading to the widespread use of many L. crispatus strains as probiotics. Nevertheless, despite the scientific and industrial relevance of this species, a comprehensive investigation of the genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Bacteriocins are antimicrobial peptides produced by bacteria that are released into the surrounding environment in order to enhance competitiveness toward other microorganisms for niche colonization ( 39 ). Screening for the presence of genes associated with bacteriocin production in the genomes of L. crispatus species allowed the identification of eight putative bacteriocin genes/loci (LCBs) distributed across L. crispatus strains of both human and poultry origin, with the only exception of LCBs 4 and 5, which were exclusively observed in isolates from human hosts, and LCBs 7 and 8, which were only identified in a strain of poultry origin, as previously reported ( 24 , 40 ) ( Fig. 2 ; Table S2).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…Bacteriocins are antimicrobial peptides produced by bacteria that are released into the surrounding environment in order to enhance competitiveness toward other microorganisms for niche colonization ( 39 ). Screening for the presence of genes associated with bacteriocin production in the genomes of L. crispatus species allowed the identification of eight putative bacteriocin genes/loci (LCBs) distributed across L. crispatus strains of both human and poultry origin, with the only exception of LCBs 4 and 5, which were exclusively observed in isolates from human hosts, and LCBs 7 and 8, which were only identified in a strain of poultry origin, as previously reported ( 24 , 40 ) ( Fig. 2 ; Table S2).…”
Section: Resultsmentioning
confidence: 59%
“…Furthermore, LCB 3 was negatively correlated with Streptococcus agalactiae inhibition, while LCB 4 was negatively correlated with Escherichia coli . Interestingly, LCB 3 is comprised of six genes that are predicted to encode a small peptide pheromone along with a bacteriocin immunity protein, normally transcribed together with the bacteriocin in order to protect the producer bacteria ( 41 ), a putative ABC transporter, and a two-component regulatory system ( 24 ). Bioinformatic analysis suggests that this locus corresponds to the inhibition activity against Streptococcus species ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the commonly-employed fluorometric starch degradation assay, which we describe as detecting amylopullulanase activity (encompassing both pullulanase and amylase activities), the unique relationship between pullulanase activity and lactic acid production was masked. Recent in vitro cultivation studies have shown that full length type I pullulanase ( pulA ) alleles with an intact signal peptide sequence are necessary for L. crispatus to exhibit robust growth when glycogen is supplied as a sole carbon source [46]; however, pulA was not needed for L. crispatus growth on glucose and the species has been documented growing on maltose and maltodextrin substrates in vitro [98]. Thus, although L. crispatus pullulanases may be found at low concentration or exhibit lower activity than amylases in vivo , they appear to contribute to the production of D-lactic acid in unique, but as yet poorly understood ways.…”
Section: Discussionmentioning
confidence: 99%